2007
DOI: 10.1007/s11883-007-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and cardiovascular risk reduction with PPAR agonists

Abstract: Peroxisome proliferator-activated receptors (PPARs) are transcriptional factors belonging to the nuclear receptor superfamily. Three isoforms, PPARalpha, PPARgamma, and PPARdelta, which are encoded by separate genes, have been identified. The PPARs act as gene regulators of various metabolic pathways in energy and lipid metabolism, glucose homeostasis, adipogenesis, and inflammation. Two key classes of synthetic compounds, fibrates and thiazolidinediones (glitazones), activate PPARalpha and PPARgamma, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A role for PPARγ has also been reported in the regulation of vascular tone, with PPARγ ligands inhibiting ET-1 and AT-1R expression while reducing the impact of excessive oxidative and nitrative stress [54,71]. PPARγ agonists increase AT-2R expression [54,71], and promote NO production and release [54,71,189,190], which, in turn, can activate PPARγ activity via MAPK [190]. Other studies suggest that PPARγ agonists reduce VEGF secretion, modulate VEGF-induced angiogenesis and inhibit VEGF-induced migration of endothelial cells.…”
Section: Pparsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for PPARγ has also been reported in the regulation of vascular tone, with PPARγ ligands inhibiting ET-1 and AT-1R expression while reducing the impact of excessive oxidative and nitrative stress [54,71]. PPARγ agonists increase AT-2R expression [54,71], and promote NO production and release [54,71,189,190], which, in turn, can activate PPARγ activity via MAPK [190]. Other studies suggest that PPARγ agonists reduce VEGF secretion, modulate VEGF-induced angiogenesis and inhibit VEGF-induced migration of endothelial cells.…”
Section: Pparsmentioning
confidence: 99%
“…However, whether or not currently used TZDs, pioglitazone and rosiglitazone, are protective of CVD in humans is questionable [223225]. Until now only a few large clinical trials have reported the effects of TZDs on cardiovascular events and the findings differ considerably as summarized in Table 12 [156,158,189,193,200]. …”
Section: Ppar Ligands/agonists and Their Relevance To Mets T2dm And Cvdmentioning
confidence: 99%
“…The significant benefit of the fenofibrate-simvastatin combination therapy over statins alone regarding the incidence of major cardiovascular events in patients with atherogenic ‘mixed’ dyslipidemia (moderate hypertriglyceridemia and low HDL-cholesterol) was especially important [23]. Moreover, there is accumulating evidence supporting a direct protective role for PPARα agonists in cardiomyocytes via the PPARα/IGF-1 pathway, an effect though, needing further investigation in humans [19]–[21], [24].…”
Section: Introductionmentioning
confidence: 99%
“…PPARs are presumed therapeutic targets in CVD (21). A word of caution: at present the clinical trials have not produced convincing evidence that CVD is prevented with the use of PPARalpha and PPARgamma agonists (22).…”
Section: Fibratesmentioning
confidence: 99%